You are on page 1of 2

Derivatives

Below, it is assumed a, n and m are constants.

d (nu ) = n du dx dx d dv du (uv ) = u +v dx dx dx
d ⎛u⎞ ⎜ ⎟= dx ⎝ v ⎠ v du dv −u dx dx = 1 du − u dv 2 v v dx v 2 dx

d ( u n ) = nu n−1 du dx dx
d ⎛ 1 ⎞ − n du ⎜ ⎟= dx ⎝ u n ⎠ u n +1 dx d n m (u v ) = u n−1v m−1 ⎛ nv du + mu dv ⎞ ⎜ ⎟ dx dx ⎠ ⎝ dx
d ⎛ u n ⎞ u n −1 ⎛ du dv ⎞ ⎜ m ⎟ = m +1 ⎜ nv − mu ⎟ ⎜v ⎟ v dx ⎝ ⎠ dx ⎠ ⎝ dx

d ( sin ax ) = a cos ax dx d ( cos ax ) = −a sin ax dx d ( tan ax ) = a sec2 ax dx d ( csc ax ) = −a cot ax csc ax dx d ( sec ax ) = a tan ax sec ax dx d ( cot ax ) = −a csc2 ax dx d ( sinh ax ) = a cosh ax dx

d ( cosh ax ) = a sinh ax dx d ( tanh ax ) = a sech 2 ax dx d (loga u ) = (loga e ) 1 du dx u dx d (loge u ) = 1 du dx u dx .